Project-Based Learning in Science Education: A Bibliometric Analysis of Research Trends on 21st-Century Skills - Emeiliya Sufiani; Puteri Diana Dhea Fadilah; Nindyah Fitri Pangestu (Journal of Progressive Science Education, 2026)
The rapid development of science and technology in the 21st century has increased the demand for educational approaches that foster essential competencies, particularly 21st-Century Skills, including critical thinking, creativity, communication, and collaboration. In Science Education, Project-Based Learning (PjBL) has emerged as a promising approach to support the development of these skills. However, existing studies on PjBL remain fragmented, and a comprehensive understanding of research trends in this field is still limited. Therefore, this study aims to analyze the research trends of project-based learning in science education with a focus on 21st-century skills using a bibliometric approach. This study utilized data retrieved from the Scopus database, resulting in 125 documents published between 2015 and 2026. The analysis was conducted using bibliometric tools, including Biblioshiny and VOSviewer, to examine publication trends, citation patterns, collaboration networks, and keyword co-occurrence. The results indicate a significant increase in research productivity, particularly after 2020, reflecting growing global interest in PjBL for developing 21st-century skills. Citation analysis shows that earlier studies have a strong foundational impact, while recent publications demonstrate rapid growth. The findings also reveal that research dissemination is dominated by conference proceedings, while high-impact journals contribute to knowledge consolidation. In terms of collaboration, contributions are globally distributed, with Indonesia, the United States, and China as leading countries, although international collaboration remains relatively limited. Furthermore, keyword analysis highlights dominant themes related to PjBL and 4C skills, as well as emerging trends in technology integration and student-centered learning. However, the limited presence of ethnoscience and local wisdom integration indicates a significant research gap. This study suggests that future research should focus on developing context-based learning approaches, particularly through the integration of ethnoscience into project-based learning, to enhance the relevance and effectiveness of science education.